1998
DOI: 10.1021/jo970803d
|View full text |Cite
|
Sign up to set email alerts
|

Transmetalation of Alkylboranes to Palladium in the Suzuki Coupling Reaction Proceeds with Retention of Stereochemistry

Abstract: Deuterium-labeling experiments demonstrate that the transmetalation step of the Suzuki coupling reaction of alkylboranes and alpha-iodoenones proceeds with retention of stereochemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(54 citation statements)
references
References 15 publications
2
49
0
3
Order By: Relevance
“…The authors proposed that the silver oxide played a role in accelerating a potentially slow transmetallation step. It was found that this process proceeded with good stereoretention, presumably via 4-membered transition state 39, as previously proposed by Soderquist [64] Woerpel [63] (see Sect. 3.2).…”
Section: Stereoselective Couplings Of Alkyl Boronates With Aryl or Alsupporting
confidence: 78%
See 1 more Smart Citation
“…The authors proposed that the silver oxide played a role in accelerating a potentially slow transmetallation step. It was found that this process proceeded with good stereoretention, presumably via 4-membered transition state 39, as previously proposed by Soderquist [64] Woerpel [63] (see Sect. 3.2).…”
Section: Stereoselective Couplings Of Alkyl Boronates With Aryl or Alsupporting
confidence: 78%
“…The stereochemistry of the transmetallation step in the Suzuki-Miyaura coupling of aryl and alkenyl halides with sp 3 organoboranes was independently studied by Woerpel [63] and Soderquist [64], and more recently by Jarvo [65]. Deuteriumlabelled substrates 30 and 33 were subjected to the coupling conditions and revealed a stereoretentive transmetallation step, leading to products 32 and 34, respectively (Scheme 8).…”
Section: Stereochemistry Of Various Steps In the Suzuki-miyaura Crossmentioning
confidence: 99%
“…Because the C-B bond of A is 'locked' on a specific face of the allyl unit, the reaction is enantiospecific regardless of the three pathways described above. The observed retention of configuration is the outcome of a stereoretentive transmetallation followed by a stereoretentive reductive elimination 44,45 . Whereas the occurrence of enantiomeric erosion is possible in reactions of chiral p-allyl palladium complexes 46,47 , it is observed only to a minimal extent in these sp 3 -sp 2 cross-couplings.…”
Section: Discussionmentioning
confidence: 99%
“…Independent studies by the groups of Soderquist [33] and Woerpel [34] revealed that transmetalation (RÀB 3RÀPd) occurs with retention of stereochemistry. Both groups used an NMR spectroscopic technique that takes advantage of the preference of bulky substituents on 1,2-disubstituted ethanes to adopt an antiperiplanar conformation.…”
Section: Stereochemistry Of the Transmetalation Stepmentioning
confidence: 99%